Low work function thin film growth for high efficiency thermionic energy converter: Coupled Kelvin probe and photoemission study of potassium oxide. Issue 6 (22nd May 2014) - Morini, F.; Dubois, E.; Robillard, J. F.; Monfray, S.; Skotnicki, T.
<x xml:space="preserve">Abstract</x> Recent researches in thermal energy harvesting have revealed the remarkable efficiency of thermionic energy converters comprising very low work function electrodes. From room temperature and above, this kind of converter could supply low power devices such as autonomous sensor networks. In this type of thermoelectric converters, current injection is mainly governed by a mechanism of thermionic emission at the hot electrode which explains the interest for low work function coating materials. In particular, alkali metal oxides have been identified as excellent candidates for coating converter electrodes. This paper is devoted to the synthesis and characterization of potassium peroxide K2O2 onto silicon surfaces. To determine optimal synthesis conditions of K2O2, we present diagrams showing the different oxides as a function of temperature and oxygen pressure from which phase stability characteristics can be determined. From the experimental standpoint, we present results on the synthesis of potassium oxide under ultra high vacuum and controlled temperature. The resulting surface is characterized in situ by means of photoemission spectroscopy (PES) and contact potential difference (CPD) measurements. A work function of 1.35 eV is measured which and the expected efficiency of the corresponding converter is discussed. It is generally assumed that the decrease of the work function in the alkali/oxygen/silicon system, is attributed to the creation of a surface dipole resulting from a charge transfer between the alkali metal and oxygen.